Making things happen: How employees’ paradox mindset influences innovative performance - Liu, Yanjun; Zhang, Hui (Frontiers in Psychology, 2022)
Individual innovation involves many contradicted behavioral options such as creative versus habitual actions, explorative versus exploitative activities and so on. However, the agentic nature of innovative behaviors has been widely ignored and we know little about what factors lead individuals to approach and balance the contradictions caused from competing demands and intentionally engage in innovative behaviors. Integrating social cognitive theory and innovation paradox, we propose a chain mediating model to explain how employees with a paradox mindset realize the creative benefits through their innovative endeavors, considering role breadth self-efficacy and individual ambidexterity as two mediators. Using data collected from 480 employees paired with 100 supervisors at 3 time points, the results show that role breadth self-efficacy and individual ambidexterity play a mediating role respectively, even they sequentially play a chain mediating role between employee paradox mindset and innovative performance. Individuals who hold a paradox mindset are more likely to perceive high capability beliefs in successfully undertaking expanded roles, promoting behavioral tendencies to switch between exploration and exploitation, in turn encouraging employees to undertake more innovative behaviors. Finally, we discuss the theoretical and practical implications for promoting employees’ innovative performance from an agentic perspective. Employees with a paradox mindset are able to make creative things happen by managing the tensions between exploration and exploitation proactively. Thus, organizations may try to enhance employees’ proactive motivation states and behavioral capability to encourage individual innovation.